DIFFERENCES IN ACCURACY OF PASSING THE BALL IN YOUNG BASKETBALL PLAYERS OF DIFFERENT LEVELS OF COMPETITION - Marta Tomljanović; Goran Jelaska; Srđan Prodanović (The Sky)
This research determined the differences in accuracy between junior basketball players at the federal and regional competition level. In this research, the following four tests were used to assess precision: Elevation precision of passing with one hand; Elevation precision of passing with two hands; Shooting a ball that bounces after falling from a height of 3.05 meters directly into the target; Shooting a ball that bounces after falling from a height of 3.05 meters with a mandatory bounce from the ground. No statistically significant differences in accuracy were found between basketball players of the federal and regional level of competition, so hypothesis X1 cannot be accepted.The conclusions reached based on the discussion of the results indicate that the accuracy of passing the ball is not one of the factors that contributes to the difference in quality between basketball players in the junior age who compete in different ranks of the competition. Also, good systematic work in the clubs and good orientation and selection of basketball players in the tested clubs contribute to the quality development of motor skills in general, which do not contribute to differences in basketball players of different levels of competition in younger selections. In further work, it is necessary to further investigate precision as one of the least researched fields of motor skills.